Selection and study of methods for implementing a diagnostic model for compressor stations of the rocket and space complex - A. V. Burakov; R. R. Khotsky; L. G. Kuznetsov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article considers a compressed air system as an object of diagnosis, which is part of a complex of compressor equipment for the production, storage, and distribution of gases for spaceports providing launch vehicles. A model for diagnosing a reciprocating compressor as the main device for the production of compressed air is selected, based on the analysis of characteristic malfunctions. Vectors of the state of the elements of the compressed air system have been developed based on a variety of structural parameters characterizing the technical condition of the diagnostic object. It is proposed to use wavelet analysis to process the diagnostic parameters obtained by analyzing the indicator diagrams of the stages of a reciprocating compressor.